Pengetahuan dan Nilai Dalam Masyarakat Terkait Penggunaan Kontrasepsi Suntik pada Akseptor KB - Anjelita Helvi Babulu; Petrus Romeo; Enjelita M. Ndoen (Universitas Nusa Cendana, 2019)
Injectable contraception is highly effective contraception, but it is not recommended for acceptors aged 35 years and over. Injection contraceptive acceptors in the working area of Puskesmas Naibonat, aged 35 years and above, reached 80%. This study aimed to determine the relationship between predisposing factors and the type of use of injectable contraceptive methods in the working area of Puskesmas Naibonat Kupang. The research was an analytical survey with a cross-sectional approach. Samples were 88 injection acceptors. Data was collected through interviews and analyzed using the Chi-Square test. The results showed that the level of knowledge (p=0,015) and values in the community (p=0,005) correlated to the use of injectable contraception, while family income was not related to the use of injectable contraceptive type (p=0,656). Health workers should provide effective communication about the selection of contraception